Early Education Innovation at Elementary School in Pandemic Covid 19 Era - Salmon Charles Siahaan; Florence Pribadi; Natalia Yuwono; Imam Santosa; Bella Meylani Lifindra; Azyvati Karensa Putera; Cassey Clarissa Gondo (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The Grand Convalescene event was divided into handbook socialization and webinars with